A new auditing mechanism for open source NoSQL database a case study on open source MongoDB database - Mohamed, Hany Heidar Hussein (2015)
MongoDB as a NoSQL database management system is relatively new on the database market and it is used in many important projects and products. Security analysis for MongoDB revealed that it doesn’t provide any facilities for auditing actions performed in the database. Recently, MongoDB company tried to rectify the auditing gap by providing MongoDB new enterprise version 2.6 (8th of April 2014). The auditing system logs operations information including; schema data definition language operations and operations related to replica set in addition to operations of authentication and authorization, and eventually general operations. But unfortunately still cannot record Data Manipulation Language (DML). Thus, this study aims to improve the auditing functionality in MongoDB by presenting a new mechanism for auditing NoSQL MongoDB database to include Data Manipulation Language (DML)/ CRUD (Create, Read, Update and delete) operations.